Pengaruh Pariwisata terhadap Pertumbuhan Ekonomi di Indonesia - Anggita Permata Yakup; Tri Haryanto (Bina Ekonomi, 2019)
The tourism sector has an important role as one of the sources for foreign exchange earnings, and can encourage national economic growth. This study examines the effect of tourism on economic growth in Indonesia based on time series data during the years 1975 - 2017. This study uses a simultaneous equation model estimated by Two stage least square. The results show that tourism has a positive effect on economic growth and conversely economic growth has a positive effect on tourism. Another factor that influences the demand for tourism in Indonesia is the exchange rate and inflation.